2020
DOI: 10.1021/jacs.0c11057
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Boosted Solar Water Oxidation by Nonconjugated Polymer-Mediated Tandem Charge Transfer

Abstract: Conjugated polymers are deemed as conductive carrier mediators for engendering the π electrons along the molecular framework, while the role of nonconjugated insulated polymers has been generally overlooked without the capability to participate in the solar-powered oxidation–reduction kinetics and charge-transfer process. Alternatively, considering the ultrashort charge lifetime and significant deficiency of metal nanocluster (NC)-based photosystems, the fine tuning of charge migration over atomically precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 52 publications
(98 reference statements)
3
49
0
Order By: Relevance
“…Our previous work on solid-state non-conjugated polymers has indicated that the solar-to-current conversion efficiency of semiconductors can be significantly improved by judiciously harnessing PEs as the intermediate charge mediator to craft unidirectional vectorial charge transport pathways in photoelectrochemical (PEC) cells. 33 In this case, the PEs not only act as a molecular binder to enable LbL assembly, but also facilitate enhanced charge transfer without causing detrimental defects. 34–37 This inspired us to rationally design tunable charge transport pathways between atomically precise metal NCs and semiconductors in heterostructured photoelectrodes for PEC water splitting with the assistance of PEs.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work on solid-state non-conjugated polymers has indicated that the solar-to-current conversion efficiency of semiconductors can be significantly improved by judiciously harnessing PEs as the intermediate charge mediator to craft unidirectional vectorial charge transport pathways in photoelectrochemical (PEC) cells. 33 In this case, the PEs not only act as a molecular binder to enable LbL assembly, but also facilitate enhanced charge transfer without causing detrimental defects. 34–37 This inspired us to rationally design tunable charge transport pathways between atomically precise metal NCs and semiconductors in heterostructured photoelectrodes for PEC water splitting with the assistance of PEs.…”
Section: Introductionmentioning
confidence: 99%
“…Polyelectrolytes (PEs), which are dened as polymers with positively or negatively charged properties in repeating monomeric units, 22,23 have been extensively utilized as surface charge modiers to fabricate spatially multilayered multi-dimensional nano-architectures in a precise, controllable and exquisite manner at the nanoscale level. [24][25][26][27] In these ways, PEs mainly play a crucial role as self-assembly initiators, by which oppositely charged building blocks are well organized into well-dened heterostructures. However, utilizing PEs that are mainly composed of non-conjugated polymers as the carrier mediator to regulate the vectorial charge transport pathways has so far not yet been reported in terms of their intrinsic insulating properties in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…This is heavily dependent on the elaborate interface engineering and constructing metal NCs-involved composite photocatalysts or photoelectrodes to achieve regulated charge transfer of metal NCs. As demonstrated in our recent work, 52 tailor-made atomically precise metal NCs, [e.g., Au x @GSH NCs, Au 25 (GSH) 18 NCs] were alternately integrated with the ultrathin polyelectrolyte (PDDA) interim layer on the metal oxides (MOs: TiO 2 , WO 4a). In this well-defined multilayered heterostructure, the intermediate PDDA layer functions as an unexpected interfacial charge mediator to regulate the carriers transport over metal NCs from the LUMO level to the CB of MOs substrates in a tandem charge transfer fashion (Figure 4, parts b and c).…”
Section: Charge Modulation Strategies Of Metalmentioning
confidence: 99%
“…(a) Schematic illustration of the PEC water oxidation mechanism of MOs–[PDDA–Au x (Au 25 )@GSH] n multilayered heterostructure. LSV (scan rate: 5 mV s –1 ) curves of WO 3 –(PDDA–Au x ) 2 , WO 3 –(Au x ) 2 , WO 3 –(PDDA) 2 , and WO 3 NPAs under (b) simulated solar light (AM 1.5G) and (c) visible light (λ > 420 nm) irradiation using Na 2 SO 4 (0.5 M, pH = 6.69) aqueous solution as the electrolyte . Reprinted with permission from ref .…”
Section: Charge Modulation Strategies Of Metal Ncsmentioning
confidence: 99%